Essays on Family Firms - Haoyong Zhou (Copenhagen Business School (CBS), 2012)
The dissertation examines corporate performance and capital structure of family firms, contributing to the limited empirical research on family firms. Family firms are prevalent in national economies all over the world. It is the prevalence that makes family firms receive increasing attentions from academia. The dissertation consists of an introduction and three chapters. Each chapter is an independent paper. The first chapter is a joint work with Professor Morten Bennedsen and Dr. Markus Ampenberger. The version of in the dissertation will be published as Chapter 6 in the forthcoming Oxford Handbook of Entrepreneurial Finance by Oxford University Press. The second paper and third paper are single-authored papers. In the first chapter, we discuss the capital structure of family firms, with a focus on the debtequity mix. Two parts comprise the chapter. In the first part, we provide a literature review on existing theoretical and empirical research in the capital structure of family firms. The literature review shows that the most important theories to explain capital structure in family firms seem to be risk aversion, agency theory, and control considerations. We argue that risk aversion and control considerations have opposing impacts on the optimal choice of debt leverage of family firms. On one hand, controlling families of family firms are typically non-diversified investors with most of their wealth and human capital tied to the company and consequently family firms use less debt. On the other hand, controlling families want to maintain the control over their companies. This control consideration restricts the willingness to raise new equity outside the family and therefore often lead to a stronger dependence on banks and other debt instruments. The literature review also shows that evidence on capital structure choices of family firms is inconclusive. Large-scale evidence on private family firms is almost missing.
hdl:10398/8607
Keywords: 650